Masojid Ni Boru; Anti Tesis Hegemoni Patriarki Berbasis Kearifan Lokal pada Etnis Batak Angkola - Ramadhanti, Zayyan; Rionaldo, Muhammad; Nadria, Aini Tasya; Wegina, Tita Wilda; Saputra, Sahran (Jurnal Intervensi Sosial dan Pembangunan, 2024)
This research aims to reveal forms of gender responsiveness in Angkola Batak culture towards the needs of women in Sipogu Village. Using qualitative methods with an ethnographic approach, this research focuses on social interactions and local wisdom that support gender equality. Informants were selected using purposive sampling, consisting of 15 sources considered most relevant to this research. Data was collected through in-depth interviews, participant observation, and ethnographic recording, which was then analyzed using NVivo software for data visualization. The research results show that the presence of Masojid Ni Boru, a public facility specifically used by women, confirms the existence of gender equality in Angkola Batak culture which refutes the results of previous research regarding patriarchal dominance in Batak society. These findings indicate that local wisdom in Sipogu Village shows unique gender responsiveness.Keywords: Masojid Ni Boru, Gender Responsiveness, Batak Angkola